The Structure and Nature of Political Philosophy in the Thought of Muslim Philosophers of the Islamic Period of Iran - Barkhordari, Aref (International Journal of Social Sciences and Management, 2020)
The present paper with a focus on the analytic-historical method and the study of the works of Iran’s Muslim philosophers in the Islamic periods is an explanation of the structure and nature of the political philosophy of Muslim philosophers in the Iran Islamic period. Political philosophy in the Islamic period of Iran is divided into two middle and new periods. The middle period starts from the arrival of Islam in Iran, and continues until the arrival of modern thought to Iran, i.e. the Constitutional Revolution. In this period, political philosophy has a tendency toward unity with religion and the rules of production of thought and political philosophy have been based on the domination of religious texts and the function of reason is simply summarized in the unambiguous explanation of the opinions of the ancients. The works of philosophers in this period are limited to the writings of the past, and gradually the tradition of margin writing becomes common. Typically, in this period, political philosophy becomes the guidance writing, diplomacy writing, tradition writing and at the same time adopts an authoritative commentary. In the new period of political philosophy, following the first period, it seeks to revive traditional concepts, and intellect and thought are seeking to be interpreted, with the difference that authoritarianism disappears. In other words, in the second period, in both fields of political philosophy and authoritarianism, we face a kind of void. Int. J. Soc. Sc. Manage. Vol. 7, Issue-4: 256-265